TOWARDS A UNIVERSAL BASIC INCOME. AN EVOLUTIONARY APPROACH - BUTARU, Lucian T. (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
Contemporary research endeavors and discussions addressing the issue of Universal Basic Income are usually concerned with the ethics, economic feasibility, and social necessity of its introduction. I believe that these approaches suffer most often due to their focus on an insufficiently extensive period of time, which does not aid in the elimination of the reluctance observed concerning their futuristic and utopian character. Accordingly, I propose the use of an analytical framework developed by evolutionary anthropologists, with the help of which we can better observe the inadequacy, unjustified and potentially dangerous limitations that cultural bias still imposes on economic activities. The central thesis of this article is that all signs indicate that we are moving into a fourth evolutionary stage of civilization, and the radical nature of the changes taking place in infrastructure, structure and superstructure will inevitably force a shift in the surviving elements of the old system, especially pertaining to the relations of production and relations of distribution. According to this approach, one can better observe that proposals such as the Universal Basic Income are more realistic (and necessary) than what the dystopias that still structure the mainstream political and economic imaginary would allow us to believe.